A Review Of The Technology Of Glass Recovery From MSW ? Introduction - Hugh R. Rhys (Society for Mining, Metallurgy & Exploration, 1975)
The question of the desirability of recovering cullet from MSW in order to recycle it into the manufacturing of glass containers remains a controversial one. The main factors appear to be: 1. The position of the Glass Container Manufacturers Institute (GCMI), as the trade association for most container manufacturers, is that post-consumer cullet is a vital source of raw material. Present requirements are for: a) Flint cullet b) Non-flint cullet of known mix proportions c) Mixed unsorted cullet of known mix propertions c) Mixed or non-flint cullet of unknown mix proportions. A market balance for these products exists, and this might somewhat limit the outlets for (b), (c) and (d), or severely limit the outlet for (d) alone. 2. The color specifications are rather strict. With cullet admixtures of 20% of the melt or more, and the use of decolorisers in a flint furnace discouraged because their action is reducing in a process which requires an oxidising environment, color contamination in a flint furnace is serious.. For amber and green furnaces (reducing) it is less serious, but in order that the quantity of decolorisers may be controlled, the color balance (as a measure of the Fe and Cr content) of the admixtured cullet should be known. 3. Why not simply color analyze, either by a continuous on-stream or off-stream: photo-electronic analysis, or by systematic batch sampling (with some kind off electronic surveillance of the mainstream) and just send mixed, color measured cullet to only amber and green furnaces? The flint would-be simply included in the mix. This is probably technically feasible, but is subject to the market limitations noted in point1.